Reimagining the family : lesbian mothering in contemporary French literature - Payne, Robert (Studies in contemporary women's writing, 2021)
"Reimagining the Family is the first book-length study of representations of lesbian mothering in French literature. Focusing on female-authored texts published between 1970 and 2013, the book explores how literature reflects, engages with and even anticipates the recent, highly charged debates on the rights of same-sex couples and parents in France. Centred around the notion of 'reimagining', the book examines how literature interrogates the normative definition of the family as a heterosexual, biological unit. It discusses a range of themes, including the difficulty of reconciling lesbianism with mothering, the role of the father, the identity of the co-mother and issues of difference and equality. The corpus includes both well-known and previously unstudied authors, and covers a range of genres, from autobiography to popular fiction. Collectively, the texts offer privileged insights into the increasingly relevant experiences of lesbian mothers and illustrate the changing face of the family in twenty-first-century France"--
Keywords: 2000-luku; lesbot; äidit; kirjallisuus; ranskankielinen kirjallisuus; naiskirjallisuus; perheet; Lesbian mothers in literature; French literature : 20th century : History and criticism; French literature : 21st century : History and criticism; French literature : Women authors : History and criticism; Families in literature